Driver genes for metastasis of colorectal cancer - Lee, L (2017)
Cancer metastasis is the principal cause of death in patients with solid organ tumours. Once cancer has spread, it is generally considered incurable. This spread of cells from the primary tumour to distant sites (metastasis) is a complex process and this DPhil focuses on colorectal cancer (CRC) metastasis. It has three aims; the development of a new CRC metastasis model, the completion of a whole-genome screen for drivers of metastasis and the development of a greater understanding of the molecular drivers of metastasis through use of human lymph node metastasis (LNM) samples. The new CRC metastasis model is a mouse model utilising endoscopeguided orthotopic transplantation of tumour cells in combination with in-vivo imaging. This model has allowed the analysis of the role of the differentiation factor, Serum/Glucocorticoid regulated Kinase 1 (SGK1) in preventing metastasis and tumorigenesis. I provide preliminary data suggesting that the inhibition of metastasis by re-expression of SGK1 is associated with the down-regulation of the transcription factor Avian Myelocytomatosis Viral Oncogene Homolog (c-MYC), and low SGK1 is a poor prognosis biomarker identifying CRC patients with high risk of disease recurrence/death. A genome-wide clustered regularly interspaced short palindromic repeats (CRISPR)/cas9 screen was then performed to identify other genes that play important roles in CRC metastasis. The screen involved the orthotopic transplantation of the MC38 line in a mouse model of metastasis and subsequent analysis using targeted next generation sequencing. This approach identified the pioneer transcription factor, Forkhead Box F1 (FOXF1) as an important regulator of metastasis. I demonstrate that FOXF1 is down-regulated in human metastatic lesions, including LNM, liver and lung metastases. Metastasis driven by low FOXF1 is mediated through Mammalian Target of Rapamycin Complex (MTORC) signalling through transcriptional control of Regulatory Associated Protein of MTOR Complex 1 (RAPTOR). Finally, I performed an analysis of 69 stage III paired CRC tumour-LNM human specimens. Metastasis in this cohort was mediated through a number of important genes and gene networks, including C-X-C chemokine receptor type 4 (CXCR4) and Kirsten Rat Sarcoma Viral Oncogene (KRAS) signalling. Non-hierarchical clustering was performed and identified two distinct subsets of LNM, LNMS1 and LNMS2 each conferring different prognoses. I have also identified different immune profiles within the "Lymphoid ecological niche" using gene expression profiling. This has enabled me to demonstrate an association between a patient's immune profile, particularly activation of CD8 cells and KRAS signalling within the tumour, with improved disease free survival in stage III CRC patients.